The Bio-Pedagogical Paradox of School Feeding Programs: Evaluating Cognitive Readiness, Moral Compliance, and Food Waste in a Faith-Based Primary School - Uswatun Hasanah; Istika Nurdiana; Roza Kusuma Dwi Arianthi; Aisyah Ratu Bunga Nirwana; Alfiandy; Alzeera Rahma Nur Aisha; Mutiara Izzati Ahmad; Nayyara Bittaqillah Suhaa; Sulthan Yafli Abhirath Anas (Universitas Islam Lamongan, 2026)
Global educational paradigms increasingly recognize school feeding programs as critical engines for holistic child development. However, existing literature predominantly evaluates these programs through long-term clinical metrics, leaving a gap in understanding the theoretical and practical tension between immediate academic stimulation and behavioral dietary compliance within highly disciplined educational settings. This study evaluates the behavioral and physiological dynamics of a national nutritional initiative using a quantitative descriptive framework. Data were systematically collected from 63 students in a faith-based primary school using a cross-sectional survey with a validated 4-point Likert scale questionnaire. The findings reveal a striking bio-pedagogical paradox. The intervention functioned as a strong catalyst for cognitive readiness, with 96.9% of participants reporting a significant increase in afternoon learning focus (Mean = 3.88). Additionally, the program demonstrated successful socio-religious conditioning, evidenced by a 93.1% compliance rate in mealtime prayers (Mean = 3.72). Conversely, deep-seated sensory aversions generated resistance to vegetable-based menus, resulting in substantial plate waste; only 61.2% of students reported responsibility in finishing their food without leftovers (Mean = 2.45), despite high moral compliance in ritualistic settings. These empirical insights challenge the assumption that institutional moral discipline naturally translates to physical dietary responsibility. To resolve this, the study advocates for a shift toward responsive institutional management. Operationally, school administrators must actively adjust menus based on continuous student feedback regarding visual presentation. Pedagogically, teachers must dedicate specific guided mealtime sessions to actively mentor students through sensory aversions, rather than relying solely on abstract moral instruction.